Lateral to medial fibro‐adipogenic degeneration are greater in infraspinatus than supraspinatus following nerve and tendon injury of murine rotator cuff. Issue 1 (14th September 2020) - Wu, Genbin; Hu, Vivian J.; McClintick, Daniel J.; Gatto, Jonathan D.; Aderibigbe, Temidayo; Lu, Liangyu; Jensen, Andrew R.; Dar, Ayelet; Petrigliano, Frank A.
Abstract: Small animal models of massive tears of the rotator cuff (RC) were introduced a decade ago and have been extensively used to study the pathophysiology of chronically injured RC. Transection of rodent suprascapular nerve and RC tendon results in progressive muscle atrophy, fibrosis and fat accumulation and affect the infraspinatus and supraspinatus muscles similarly to that seen in the setting of massive RC tears in humans. The purpose of this study was to perform a comprehensive and detailed analysis of the kinetics of fibrotic scar and adipose tissue development comparing phenotypic differences between chronically injured infraspinatus and supraspinatus. Automatic mosaic imaging was used to create large image of whole infraspinatus or supraspinatus sectioned area for quantification of spatial heterogeneity of muscle damage. Pathologic changes advanced from the lateral site of transection to the medial region far from the transection site. A prominent, accelerated muscle fibrosis and fat accumulation was measured in injured infraspinatus compared to supraspinatus. Furthermore, adipose tissue occupied significantly larger area than that of fibrotic tissue in both muscles but was greater in infraspinatus within 6 weeks post induction of injury. Our findings confirm that infraspinatus is more susceptible to accelerated chronic degeneration and can be used to identify the physiological functions that distinguish between the response of infraspinatus and supraspinatus in the setting of massive tears. Whether these pathologic differences observed in mice are reflected in humans is one key aspect that awaits clarification.